DEVELOPING WEB-BASED MEDIA TO PROMOTE STUDENTS 'INITIAL CRAFTS - Amalia, Tina; Hanavi, Ivan; Sastrawijaya, Yuliatri; Jarudin, Jarudin (JURNAL SISFOTEK GLOBAL, 2021)
Training entrepreneurs is very important to equip students' skills in community life. The students' products in this aspect of handicrafts have been promoted by displaying them in glass cabinets.. Some works are sold directly by students to friends who are interested in buying handicraft products produced. Works that have long been displayed in glass cabinets are usually discarded and replaced by students' work the following year. This is unfortunate because there is no media promotion of students' handicrafts, the purpose of this research is to develop web-based promotional media to promote students' pre-work handicrafts. The method used in this research is by kuantitativ research and development approach. The instrument used kuesioane with a scale of five options liker. Involving 60 participants in product trials divided into two groups, three expert teams for product validation and 57 participants for product trials. The results of the study based on the validation team that the media is feasible to be used as a means of promotion of student handicraft products, while the results of the trial that web-based media is effective to promote the results of student pre-work handicrafts. Kesimpulnya that the products produced can be used as a means of conveying information to the wider community both nationally and globally indefinitely. The implication of this study is to facilitate marketing regardless of the level of the economy in all directions.